Visual Arts in Digital and Online Environments: Changing Copyright and Fair Use Practice among Institutions and Individuals Abstract - Aufderheide, Patricia; Sinnreich, Aram (AoIR Selected Papers of Internet Research, 2016)
This study measures changes in behavior and attitudes about fair use among visual arts professionals, the future of whose field depends on advancing into online, digital environments that depend upon it. A survey of 2,394 visual arts professionals demonstrated broad awareness of and actions using a then-months-old Code of Best Practices in Fair Use for the Visual arts. It also shows some lack of confidence in understanding the law among those who are familiar with the code. As well, changes were less evident in the area most vulnerable to self-censorship: the digital and online realm.